Wolverines and Deadpools : claws & mercs - Ziglar, Cody; North, Ryan, 1980-; Gage, Christos (Marvel Worldwide, Inc., 2026)
What's better than The Best There Is partnered up with the Merc With the Mouth? How about adding daughters Ellie Camacho and Laura Kinney to the mission as they go up against a classic X-Villain? It's Wolverines and Deadpools, baby - in the clutches of the Shadow King! But who is he really after? Plus: Logan and Wade Wilson on an adventure though time and space, hacking and slashing their way through the Multiverse on an epic quest of heroism - and friendship! And the same two superstars at each other's throats in Madripoor!